Influence of Smoking on Academic Performance of Undergraduate of Students at Ajman University - Muhammad, Maryam Bala; Sani, Jamila (Direct Research Journal of Health and Pharmacology, 2024)
The study presents a comprehensive examination of the influence of smoking on the academic performance of undergraduate students at Ajman University, emphasizing the complex interplay between smoking behaviour, health outcomes, and educational achievements. It discusses the prevalence of smoking among students and highlights the need for targeted interventions to address this issue effectively. The study employed a survey method to collect data from a sample of undergraduate students, revealing insights into their smoking habits, age of initiation, attempts to quit, parental awareness, and perceived influences. Statistical analysis of linear regression demonstrated a significant influence of smoking on academic performance, with smoking behaviour being a significant predictor. The findings underscore the importance of promoting non-smoking behaviour among students and implementing campus-wide smoking cessation programs. Recommendations include encouraging students to avoid smoking and implementing strict no-smoking policies within the university premises. Overall, the study contributes to a better understanding of the relationship between smoking and academic success, emphasizing the need for comprehensive approaches to promote student well-being and success.
Keywords: Smoking; academic performance; undergraduate students and Ajman University